2006
DOI: 10.1063/1.2158516
|View full text |Cite
|
Sign up to set email alerts
|

Density determination of focused-electron-beam-induced deposits with simple cantilever-based method

Abstract: Freestanding deposits are grown on a silicon cantilever from a precursor gas by an electron induced process. Deposit mass determination is performed with an atomic force microscopy setup, where the cantilever resonance frequency shift, resulting from mechanical removal of the deposit, is measured. Deposits from hexafluoroacetylacetonato-Cu͑I͒-vinyltrimethylsilane show densities ranging from 2.05± 0.45 to 3.75± 0.55 g / cm 3 . Deposits from tetramethoxysilane have a constant density of ͑1.9± 0.3͒ g/cm 3 . Densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 16 publications
(13 reference statements)
5
42
0
Order By: Relevance
“…The density of tips deposited from tetramethyl ortho-silicate ͑TMOS͒, hfac-Cu-VMTS, and Co 2 CO 8 has been measured for beam currents of 0.1, 1, and 100 nA. 66 It was found that the density of the deposit from TMOS is independent of the beam current used. For deposits from hfac-Cu-VMTS both the density and the metal content increased with increasing beam current.…”
Section: Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The density of tips deposited from tetramethyl ortho-silicate ͑TMOS͒, hfac-Cu-VMTS, and Co 2 CO 8 has been measured for beam currents of 0.1, 1, and 100 nA. 66 It was found that the density of the deposit from TMOS is independent of the beam current used. For deposits from hfac-Cu-VMTS both the density and the metal content increased with increasing beam current.…”
Section: Densitymentioning
confidence: 99%
“…Folch and Servat 64 came to the same conclusion based on experimental data. However, Bret et al, 65 Randolph et al, 40 and Utke et al 66 assumed that the increase in temperature can be as much as 60-80°C for tip depositions. The sharp decrease in growth efficiency for contamination in Fig.…”
Section: Temperaturementioning
confidence: 99%
“…For example, it has been observed that increasing the power density of the incident electron beam and/or decreasing the steady-state concentration of the precursor during deposition results in an increase in deposited metal content although no study to date has produced 100% metallic purity using such a strategy. 10,22,[33][34][35][36][37][38] Substrate annealing during deposition decreases the residence time for both the adsorbed precursors and the volatile products of dissociation, and also effectively increases the purity of deposits formed by FEBIP. [39][40][41] Postdeposition annealing, either in situ or in the presence of a reactive species, can also result in increased deposition purity.…”
Section: mentioning
confidence: 99%
“…The matrix density was assumed ϳ1.5 g cm −3 . 15 An equivalent deposition experiment was performed using the FEB ͑5 kV, 0.8 nA͒ resulting in a deposit density of deposit = ͑4.5± 0.5͒ g cm −3 . A Pt content of 15 at.…”
mentioning
confidence: 99%